Surgical treatment of patients with ankle joint fracture and damage of syndesmosis - Kozhemyaka, Maksym; Golovakha, Maksim (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Treatment of unstable ankle joint fractures with damage of syndesmosis is one of important problems in modern traumatology practice. Objective: to evaluate the results of surgical treatment of patients with ankle joint fractures and damage of syndesmosis due to analysis of functional ankle state and assessment of life quality in postoperative period. Methods: we analyzed the results of surgeries of 80 patients (18–67 y. o.) with ankle joint fracture and damage of syndesmosis. In all cases we made osteosynthesis and restoring of syndesmosis stability with following course of rehabilitation, which was the same in our groups. In the main group 44 patients we used developed devices (modeling plates with polyaxial screws blocking for external malleous and tight loops for syndesmosis stabilization). In comparative group (36 patients) we used method АО/ASIF (for external malleous we used AO ⅓ and 1–2 cortical screws of 3.5 mm for syndesmosis fixation). We assessed the results of treatment in 3, 6, 12 months after surgery with 100 score Ankle-Hindfoot Scale AOFAS and SF-36 system. Results: it was established that in the early terms after surgery (3 mon.) in the main group the functional results were better according to AOFAS scale on 17 %. The quality of life according to SF-36 was also better: the signs of physical condition — 21 %, psychological — 7.4 %. Conclusions: suggested method combines stable osteosynthesis of external malleous fractures with stable dynamic fixation of syndesmosis, it allow in improve the life quality and to get excellent and good results in 95.5 % cases.